Heating-and-air conditioning servicer - Clinton, Susan (Mankato, Minn. : Capstone Books, 1998)
Outlines the educational requirements, duties, salary, employment outlook, and possible future positions of heating-and-air conditioning servicers.
Includes bibliographical references and index.
Keywords: Heating -- Equipment and supplies -- Maintenance and repair -- Vocational guidance; Air conditioning -- Equipment and supplies -- Maintenance and repair -- Vocational guidance; Heating -- Equipment and supplies -- Maintenance and repair -- Vocational guidance; Air conditioning -- Equipment and supplies -- Maintenance and repair -- Vocational guidance; Vocational guidance